2016
DOI: 10.21475/ajcs.2016.10.05.p7491
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variability and genetic relationships of date palm (Phoenix dactylifera L.) cultivars based on inter-primer binding site (iPBS) markers

Abstract: Date palm (Phoenix dactylifera L.) is an important fruit crop in many arid areas and understanding the relatedness among genotypes is important for effective date palm improvement. Inter-primer binding site (iPBS) markers were used to assess the molecular variation and genetic diversity of 54 and 12 date palm (Phoenix dactylifera L.) genotypes collected from Australia and Iraq, respectively. The main objectives were to survey genetic diversity and to determine varietal differences among the collected date palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
3
15
1
Order By: Relevance
“…Accurate identification of accessions in a germplasm collection is an important first step in crop improvement. Molecular marker systems, including SSRs, can more accurately differentiate germpalsm than methods based on morphological traits or isoenzymes because they are objective, reproducible and independent of environmental influences (Al-Najm et al, 2016;Mehmood et al, 2016). In the current study, seventeen polymorphic SSR markers discriminated a range of Phoenix dactylifera accessions including related species and provided valuable information on the genetic relationship amongst the accessions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accurate identification of accessions in a germplasm collection is an important first step in crop improvement. Molecular marker systems, including SSRs, can more accurately differentiate germpalsm than methods based on morphological traits or isoenzymes because they are objective, reproducible and independent of environmental influences (Al-Najm et al, 2016;Mehmood et al, 2016). In the current study, seventeen polymorphic SSR markers discriminated a range of Phoenix dactylifera accessions including related species and provided valuable information on the genetic relationship amongst the accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is similar to that of Elhoumaizi et al (2006) who showed that the Moroccan cultivar Medjool, collected from different geographical regions, had a significant range of genetic variation. These observations suggest that targeted intra-varietal selection of major date cultivars such as Medjool, Barhee and Deglet Noor could be an effective crop improvement strategy (Al-Najm et al, 2016). Date palm breeding in Iraq is highly dependent upon seed propagation and subsequent selection based on specific characteristics important to local farmers such as fruit quality and plant vigor (Khierallah et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations